Visionary of the principal leadership in improving the quality of learning - Atika, Murti; Harapan, Edi; Rohana, Rohana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Through education, it is hoped that future generations will have the skills, talents, and attitudes of quality that can respond to competition in the age of globalization. In order to increase the quality of learning, the innovative leadership of school principals has a significant role to play.The goal of this study was to explain the principal's vision of improving the standard of learning and the barriers to visionary leadership at SMA Negeri 1 BabatSupat. In this research, through questionnaire, evaluation and observation, using qualitative approaches and data collection techniques. Data analysis used data reduction, data presentation and vehicle analysis in this research Conclusion or verification. The authenticity of creditable, transferable, defensible and verifiable data the findings showed that : (1) The principal's vision of enhancing the standard of learning at SMA Negeri 1 BabatSupat is to realize: